THE EFFECT OF FIELD WORK PRACTICES ON WORK INTEREST OF CLASS XII STUDENTS OF ACCESS NETWORK ENGINEERING SKILLS COMPETENCE AT SMK NEGERI 5 TELKOM BANDA ACEH - Husnizar Husnizar; Fathiah, Fathiah; Agus Fachruzi (Multica Science and Technology (ACCREDITED-SINTA 5), 2022)
Education is a foundation for improving the quality of human resources. Quality education will be able to produce superior human resources from every aspect of life. One of the educations that is responsible for creating quality human resources is Vocational High School (SMK) education. Vocational learning load includes Face-to-face (TM) School Practice (PS) activities and Practical Activities in DU/DI. Field work practices can train and support the skills that students have learned while at school, so that they can be developed in the world of work. But apart from that, there are some SMKs that pay less attention to the implementation of the field work practice. The discrepancy between the material studied at school and what is faced by students in DU/DI. This study aims to determine how much influence field work practices have on the work interest of class XII students of Access Network Engineering Skills Competence at SMK Negeri 5 Telkom Banda Aceh. This study uses a quantitative approach with the method used is Ex Post Facto. The subjects of this study were 48 students of the Access Network Engineering Department. The instrument used is a questionnaire. The results of this study indicate that there is a positive influence between field work practices and work interest of class XII students of Access Network Engineering expertise competence at SMKN 5 Telkom Banda Aceh by 39.8%, while 60.2% is influenced by other factors. This study uses a quantitative approach with the method used is Ex Post Facto. The subjects of this study were 48 students of the Access Network Engineering Department. The instrument used is a questionnaire. The results of this study indicate that there is a positive influence between field work practices and work interest of class XII students of Access Network Engineering expertise competence at SMKN 5 Telkom Banda Aceh by 39.8%, while 60.2% is influenced by other factors. This study uses a quantitative approach with the method used is Ex Post Facto. The subjects of this study were 48 students of the Access Network Engineering Department. The instrument used is a questionnaire. The results of this study indicate that there is a positive influence between field work practices and work interest of class XII students of Access Network Engineering expertise competence at SMKN 5 Telkom Banda Aceh by 39.8%, while 60.2% is influenced by other factors.